Construction and validation of informative material on the milestones of oral language development: Revista 10Envolvimento (Research, Society and Development, 2022)
Objective: to validate the content of an informative material on the acquisition and development of oral language in children 0 to 5:0 years old, in magazine format. Method: The validation of the material was performed by a group of experts’ speech language therapists. The questionnaire consisted of 18 questions that addressed the following categories: content, language and design applied. Each investigated item was analyzed through the 5-point Likert scale of agreement and for each category a blank space was left for the judges to make comments. To quantitatively verify the degree of agreement between them, the Content Validity Index (CVI) with a minimum value of 80%. Regarding the qualitative analysis, a thorough analysis of the judges' comments was carried out through content analysis. Conclusion: a high index of content validity and final presentation was reached. It is expected that the material will support educational actions in health, providing the dissemination of information to family members, caregivers, as well as students and professionals involved with children in the development phase.